Presepsin for sepsis diagnosis in emergency departments: a multicentre study - Jiraporn Sri-on; Kiattichai Daorattanachai; Kittiyaporn Wiwatcharagoses; Pariwat Phungoen; Suramath Isaranuwatchai; Pitsucha Sanguanwit; Thammapad Piyasuwankul; Wisarut Bunchit; Natchapon Sinsuwan; Rapeeporn Rojsaengroeng; Korakot Apiratwarakul; Nipa Udonjarut; et al. (Emergency Medicine Journal, 2026)
OBJECTIVES: To evaluate the diagnostic accuracy of presepsin and procalcitonin (PCT) for sepsis and septic shock (Sepsis-3) in the emergency department (ED) based on the Sepsis-3 definition, where early diagnosis remains challenging due to the lack of rapid and reliable diagnostic methods. METHODS: This multicentre prospective cohort study recruited adults from eight EDs in Thailand between October 2020 and June 2022. Patients with suspected infection or those who met the quick Sequential Organ Failure Assessment criteria were enrolled. Admission blood samples were analysed for presepsin, PCT, lactate and blood culture, with follow-up presepsin and PCT measurements performed on days 3 and 7, and follow-up for 30-day mortality. Sepsis diagnosis was adjudicated with reference to the Sepsis-3 criteria and blood culture result. Diagnostic accuracy metrics, including the area under the receiver operating characteristics curve (AUROCs), sensitivity, specificity and predictive values of presepsin and PCT were evaluated. RESULTS: Of 668 included participants, 438 (65.6%) were diagnosed with sepsis and 58 (8.7%) with septic shock. Presepsin levels were significantly higher in patients with Sepsis-3 than in patients without sepsis at ED admission and decreased over time. Presepsin exhibited a slightly higher AUROC for predicting sepsis (AUROC 0.63 (95% CI 0.59 to 0.67)) and septic shock (AUROC 0.73 (95% CI 0.66 to 0.80)) compared with PCT (AUROC for sepsis 0.62, 95% CI 0.58 to 0.66 and septic shock 0.72, 95% CI 0.65 to 0.78). Elevated presepsin and PCT levels were associated with increased mortality within 30 days (OR 2.61, 95% CI 1.73 to 3.92 and OR of 1.62, 95% CI 1.09 to 2.42 consequently). CONCLUSIONS: Presepsin showed slightly higher diagnostic accuracy than PCT, but overall diagnostic accuracy was modest. When interpreted together with clinical assessment and routine tests, presepsin may assist early risk stratification and support, rather than replace, clinical judgement in decisions such as resuscitation or antibiotic initiation.
Keywords: Sepsis Diagnosis and Treatment; Neonatal and Maternal Infections; Bacterial Identification and Susceptibility Testing